Cryptic species and hybridization in the Anolis polylepis complex, with the description of a new species from the Osa Peninsula, Costa Rica (Squamata: Polychrotidae) - Köhler, Gunther; Dehling, D. Matthias; Köhler, Johannes (Zootaxa, 2010)
Based on differences in hemipenial morphology we recognize two species of anoles related to Anolis polylepis: Anolis polylepis (Pacific versant of central and southern Costa Rica and western Panama, excluding the Osa Peninsula) and a species described herein which is restricted to the Osa Peninsula. The two species differ in hemipenial morphology (hemipenis bilobed in A. polylepis versus unilobed in the species from the Osa Peninsula) but show no discernable differences in external morphology (i.e., morphometrics, scalation, coloration, male dewlap). We therefore consider them to be cryptic species. At the neck of the Osa Peninsula where the ranges of the two species meet we detected a narrow (about 1 km wide) hybridization zone in which only individuals with an intermediate hemipenial morphology occur.